1996
DOI: 10.1038/ng0896-472
|View full text |Cite
|
Sign up to set email alerts
|

A full genome search in multiple sclerosis

Abstract: The aetiology of multiple sclerosis (MS) is uncertain. There is strong circumstantial evidence to indicate it is an autoimmune complex trait. Risks for first degree relatives are increased some 20 fold over the general population. Twin studies have shown monozygotic concordance rates of 25-30% compared to 4% for dizygotic twins and siblings. Studies of adoptees and half sibs show that familial risk is determined by genes, but environmental factors strongly influence observed geographic differences. Studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
286
0
7

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(297 citation statements)
references
References 25 publications
4
286
0
7
Order By: Relevance
“…Although the association of HLA class II alleles with multiple sclerosis is readily demonstrated, 8,24 the effect of this locus on susceptibility is modest and therefore evidence for linkage in this region is expected to be difficult to confirm. Previous linkage screens in out-bred populations of northern European origin (American, British and Canadian) [12][13][14] showed only modest evidence for linkage to the HLA region. Our study is in keeping with these results in that it also shows only modest evidence for linkage in the HLA-region on chromosome 6p21.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although the association of HLA class II alleles with multiple sclerosis is readily demonstrated, 8,24 the effect of this locus on susceptibility is modest and therefore evidence for linkage in this region is expected to be difficult to confirm. Previous linkage screens in out-bred populations of northern European origin (American, British and Canadian) [12][13][14] showed only modest evidence for linkage to the HLA region. Our study is in keeping with these results in that it also shows only modest evidence for linkage in the HLA-region on chromosome 6p21.…”
Section: Discussionmentioning
confidence: 90%
“…11 In multiple sclerosis, six whole genome screens for linkage have now been performed. [12][13][14][15][16][17] No one has shown unequivocal linkage, but most have identified more regions of potential linkage than expected by chance and together they provide the best available summary of the likely location of the relevant genes. 18 The high prevalence of multiple sclerosis (120/100 000) in Scandinavia 19 and the striking correlation between its global geographical distribution and the migration pattern of northern Europeans 20 suggest that important susceptibility alleles may have arisen in Scandinavia and been disseminated by their descendants-the so-called 'Viking hypothesis'.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Follow-up screenings in confirmatory and additional data sets have been completed as well (at least one additional large linkage study of 830 sib pairs using over 4500 single-nucleotide polymorphism or 'SNP' markers is in progress). Together, these studies identified approximately 60 genomic regions potentially involved in disease susceptibility, consistent with the long-held view that MS is a polygenic disorder.…”
Section: Ms Genomicsmentioning
confidence: 99%
“…4,5 Environmental factors have also been demonstrated from studies on migration and apparent epidemics. From all the genetic factors addressed, susceptibility has been clearly established with only certain MHC haplotypes in particular those containing the HLA-DR2 alleles in the Caucasian population whilst in the Mediterranean population links were found with the haplotypes containing HLA-DR4 and HLA-DR3.…”
Section: Multiple Sclerosismentioning
confidence: 99%